Modernization of Pesantren-Based Education: Study on the Use of the eNJe Santri Provision Application System in Improving the Quality of Pesantren Services - Lukman Sholeh; M. Makruf Al Arif; Slamet (Relevancia: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to analyze and understand the use of the Bekal Santri eNJe application system, as a response to the modernization of Nurul Jadid Islamic Boarding School, Paiton, Probolinggo in improving the quality of its services. This research uses a qualitative approach type of case study. Data collection techniques are carried out through observation, interviews and documentation. Data analysis starts from presenting data, reducing data and ending with drawing conclusions. The results showed that the use of the Bekal Santri eNJe application system was able to answer the challenges of modernizing pesantren and the complexity of community demands in the midst of competition between educational institutions, through the provision of services on transfer-based remittances, Teping-based Santri Shopping, and payments made digitally through virtual accounts.